Despite the pandemic: upward trajectories of medication adherence and persistence in patients with dyslipidemia - Jang, Jieun; Oh, Hyun Jung; Lee, Eui-Kyung (Frontiers in Pharmacology, 2024)
Background: Dyslipidemia, a major cardiovascular risk factor, requires consistent medication adherence, but new patients often struggle due to its asymptomatic nature. The COVID-19 pandemic has disrupted global healthcare. This study examined its impact on medication adherence and persistence among Korean patients with dyslipidemia (PWD), comparing the effects on new versus existing PWD.Method: Nationwide claims data were used to identify PWD and their prescribed medications. Patients were categorized as new or existing PWD and matched 1:1 using propensity scores in both the pre-and post-COVID-19 periods. Medication adherence was measured by the proportion of days covered (PDC), and persistence was assessed by analyzing gaps in continuous medication dispensing. The impact of COVID-19 was evaluated using multiple regression and Cox proportional hazard models.Result: The pre-COVID-19 cohort included 519,696 patients, and the post-COVID-19 cohort comprised 536,762 patients. PDC significantly increased post-COVID-19, with existing PWD showing a larger increase by 4.74 units (p <.0001), compared with 2.01 units for new PWD (p <.0001). Both groups exhibited lower risks of medication discontinuation, with a greater decrease observed in the existing PWD (hazard ratio [HR] 0.780, 95 % confidence interval [CI] [0.774-0.786], p <.0001), compared with the new PWD (HR 0.929, 95 % CI [0.923-0.934], p <.0001). New PWD had fewer annual visits, whereas existing PWD had more visits (both p <.0001).Conclusion: Despite the COVID-19 pandemic, medication adherence and persistence improved in both new and existing PWD. Notably, new patients with no prior treatment experience showed weaker positive responses, highlighting the potential need for targeted interventions to support new patients during public health crises.